Sociometric Status and Peer Control Attempts: A Multiple Status Hierarchies Approach. (January 2017) - de Klepper, Maurits C.; (Joe) Labianca, Giuseppe; Sleebos, Ed; Agneessens, Filip
Abstract: We study a population of first year midshipmen within an elite military academy to explore the relationship between individuals' sociometric status (e.g., status conferrals based on positive interpersonal affect and perceived competence, and status degradations based on negative interpersonal affect) and their attempts to directly control their peers' behaviour over a year's time. Results show that multiple informal sociometric status hierarchies develop early in the organization's life and remain remarkably stable. Control attempts are driven by these status hierarchies: Lower competence status individuals and those who attract negative status degradations are targeted for control by more people early in the group's life, those relatively free of negative status degradations attempt to control greater numbers of others throughout the group's existence, while higher positive status is generally unrelated to control attempts. However, control attempts do not lead to higher future sociometric status, suggesting they are not status signals. Findings also show that individuals targeted for control by many others leave the organization entirely.